2020
DOI: 10.1093/sleep/zsaa093
|View full text |Cite
|
Sign up to set email alerts
|

Changes in dietary inflammatory potential predict changes in sleep quality metrics, but not sleep duration

Abstract: Study Objectives Non-pharmacological sleep interventions may improve sleep profiles without the side-effects observed with many pharmacological sleep aids. The objective of this research was to examine the association between sleep and inflammation and to examine how changes in dietary inflammatory potential influence changes in sleep. Methods The Inflammation Management Intervention Study (IMAGINE), which was a dietary inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 79 publications
4
20
0
Order By: Relevance
“…The Plant-Based and Lean Proteins pattern was associated with earlier sleep timing at follow-up, as well as a more favorable change in sleep timing from baseline to follow-up. These findings align with results from a recent intervention study among adults, in which participants whose diets became more anti-inflammatory (higher in fruits, vegetables, lean proteins and lower in added sugar and saturated fat) over a 3-month period experienced improvements in sleep onset latency [32]. Specific nutrients present in the Plant-Based and Lean Proteins pattern could also help explain the findings.…”
Section: Discussionsupporting
confidence: 87%
“…The Plant-Based and Lean Proteins pattern was associated with earlier sleep timing at follow-up, as well as a more favorable change in sleep timing from baseline to follow-up. These findings align with results from a recent intervention study among adults, in which participants whose diets became more anti-inflammatory (higher in fruits, vegetables, lean proteins and lower in added sugar and saturated fat) over a 3-month period experienced improvements in sleep onset latency [32]. Specific nutrients present in the Plant-Based and Lean Proteins pattern could also help explain the findings.…”
Section: Discussionsupporting
confidence: 87%
“…In addition, supplementation with tart cherry juice (a natural fruit juice) in randomised trials among adults has been shown to improve sleep timing (9,10) and quality (10) . A possible mechanism linking 100 % fruit juice and sleep timing could be related to its anti-inflammatory potential, which has been related to higher sleep quality in some studies (32,33) . The consumption of 100 % fruit juice could also be an indicator of an overall healthier lifestyle.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in future research, it would be beneficial to combine subjective and objective methods of data collection in order to obtain more reliable and accurate results in IBS-related studies. Diet-derived sleep improvement has also been previously documented [126], and healthy adults' sleep can be negatively impacted when people shift their diet towards low fibre and high saturated fat and sugar intake [127]. Animal studies have shown that dietary prebiotics [128] and their metabolite, butyrate [68], can improve sleep.…”
Section: Sleep Hierarchical Assessment Methodsmentioning
confidence: 84%
“…Diet-derived sleep improvement has also been previously documented [ 126 ], and healthy adults’ sleep can be negatively impacted when people shift their diet towards low fibre and high saturated fat and sugar intake [ 127 ]. Animal studies have shown that dietary prebiotics [ 128 ] and their metabolite, butyrate [ 68 ], can improve sleep.…”
Section: Discussionmentioning
confidence: 99%